Altered pain sensitivity and axioscapular muscle activity in neck pain patients compared with healthy controls. (27th August 2017) - Christensen, S.W.; Hirata, R.P.; Graven‐Nielsen, T.
Abstract: Background: Previous studies have indicated that neck pain patients feel increased symptoms following upper limb activities, and altered axioscapular muscle function has been proposed as a contributing factor. Methods: Pain sensitivity and muscle activity, during arm movements, were assessed in neck pain patients and controls. Patients with ongoing insidious‐onset neck pain (IONP, N = 16) and whiplash‐associated disorders (WAD, N = 9) were included along with sex‐ and age‐matched controls ( N = 25). Six series of repeated arm abductions were performed during electromyographic (EMG) recordings from eight bilateral muscles. The first and last three series were separated by 8 min and 42 s, respectively. Each series consisted of three slow and three fast movements. Pressure pain thresholds (PPTs) were recorded bilaterally from neck, head and arm at baseline, after the third and sixth movement series. Pain intensity was recorded on an electronic visual analogue scale (VAS). Results: Larger pain areas and higher VAS scores were found in patients compared with controls ( p < 0.001), and in patients, the VAS scores increased in the course of movements ( p < 0.02). PPTs were lower in patients compared with controls at all sites ( p < 0.03), and these decreased during arm movements in the IONP group ( p < 0.03), while increasing at head and neck sites in controls ( p < 0.04). During the slow movements, increasing serratus anterior EMG activity was found in the series with short breaks in‐between for the WAD group compared with IONP and controls ( p < 0.001). Conclusion: Axioscapular movement caused different responses in pain sensitivity and muscle activity between neck pain patient groups compared with controls. Significance: Neck pain patients report increased symptoms following upper limb activities. This study shows that repeated arm movements caused differentiated responses in pain sensitivity and muscle activity between subgroups of neck pain patient and asymptomatic controls. Such findings may be of great clinical significance when planning rehabilitation for this patient population.